1997
DOI: 10.1002/(sici)1096-9896(199709)183:1<109::aid-path1091>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal protein deprivation on the fetal rat pancreas: major structural changes and their recuperation

Abstract: There is evidence that low birth weight and poor growth in early life cause a long‐term predisposition to non‐insulin‐dependent diabetes. Morphological changes were assessed in fetal rat pancreas subjected to both pre‐ and post‐natal maternal protein deprivation (LP). Further groups were subjected to purely prenatal maternal protein deprivation (preLP) and purely postnatal maternal protein deprivation (postLP), as well as a control group. The results show that the LP and postLP groups had fewer but larger isle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 21 publications
(17 reference statements)
1
22
1
Order By: Relevance
“…In the rat, maternal dietary protein restriction (approximately 40-50% of normal intake) throughout gestation and lactation has been reported to alter glucose homeostasis and hypertension in the adult offspring (34)(35)(36)(37)(38)(39). Offspring are significantly growth retarded, remain growth retarded throughout life, and in some cases develop mild ß-cell secretory abnormalities (34)(35)(36)(37)(38) and in others insulin resistance (36,39). Aged rats develop hyperglycemia characterized by defects in insulin signaling in muscle, adipocytes, and liver (39)(40)(41)(42)(43).…”
Section: What Animal Models Can Tell Usmentioning
confidence: 99%
“…In the rat, maternal dietary protein restriction (approximately 40-50% of normal intake) throughout gestation and lactation has been reported to alter glucose homeostasis and hypertension in the adult offspring (34)(35)(36)(37)(38)(39). Offspring are significantly growth retarded, remain growth retarded throughout life, and in some cases develop mild ß-cell secretory abnormalities (34)(35)(36)(37)(38) and in others insulin resistance (36,39). Aged rats develop hyperglycemia characterized by defects in insulin signaling in muscle, adipocytes, and liver (39)(40)(41)(42)(43).…”
Section: What Animal Models Can Tell Usmentioning
confidence: 99%
“…Hyperglycemia, impaired insulin secretion, insulin resistance, and even frank diabetes in the offspring have been induced by some prenatal maneuvers with or without IUGR (55,60 -66). Underlying mechanisms may include decreased number of pancreatic ␤ cells (67)(68)(69), upregulation of hepatic enzymes that may convey insulin resistance (55,60), and upregulation of the glucocorticoid receptor (60,70,71). In contrast, Gatford et al (72) reported that 5-yr-old sheep made that were hypertensive by prenatal administration of dexamethasone exhibited unchanged insulin sensitivity.…”
Section: Characteristics Of Disease In Offspringmentioning
confidence: 99%
“…4,8 For example, the offspring of rodents fed a low protein (LP) diet have fewer but larger pancreatic islets and increased sensitivity to insulin in the muscles compared with rodents fed standard diet. 9,10 Moreover, increased preference for high-fat foods was developed in utero as an effect of protein-poor fetal diet in rodents. 11,12 One of the first epidemiological studies on humans during the Dutch Hunger Winter showed that adult men whose mothers had received poor nutrition during pregnancy had increased prevalence of obesity.…”
Section: Introductionmentioning
confidence: 99%